Kinetics and Mass Transfer of Methylene Blue Adsorption onto EDA/Cu2+-Functionalized Fly Ash Silica Xerogel - Tsagifa, Faiqa Haura; Nasra, Edi; Sanjaya, Hary; Ningsih, Sherly Kasuma Warda; Gemasih, Muhammad Iqbal Saputra (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Methylene blue (MB) contamination in water bodies necessitates efficient removal via adsorption using functional materials. In this study, fly ash-based silica xerogel modified with ethylenediamine and copper(II) (SX-EDA/Cu²⁺) was synthesized and evaluated for adsorption kinetics. FTIR spectroscopy indicated the presence of amine groups and Cu²⁺ coordination on the silica matrix. Batch adsorption experiments were conducted in triplicate (n = 3) at room temperature (25 ± 2 °C), pH 5.0, with 0.1 g adsorbent in 25 mL MB solution (1000 mg/L). The adsorption capacity increased rapidly, reaching a maximum qₜ of 234.55 ± 1.23 mg/g at 60 minutes, and stabilized at an equilibrium qₑ of 229.36 ± 1.17 mg/g by 90 minutes. Kinetic data were analyzed using five models (PFO, PSO, Elovich, Intra-Particle Diffusion, and Liquid Film Diffusion) with regression and error function evaluation (R², χ², RMSE). The pseudo-second-order model provided the best empirical fit (R² = 0.9972; qₑ,calc = 217.39 ± 5.80 mg/g), while film diffusion (R² = 0.9994) and intra-particle diffusion contributed jointly to mass transfer resistance. These results indicate that SX-EDA/Cu²⁺ exhibits rapid uptake and high adsorption capacity for MB, with adsorption kinetics governed by combined film and pore diffusion processes.